2020
DOI: 10.22437/irje.v4i1.8790
|View full text |Cite
|
Sign up to set email alerts
|

Blended Learning in a Reading Course: Undergraduate EFL Students’ Perceptions and Experiences

Abstract: Research on blended learning in reading course especially is limited. This study aimed at revealing the implementation of blended learning in reading course for undergraduate EFL students at one public university in South Sumatera and the students’ perceptions on the e-learning incorporated in the blended learning in the reading course. The study was carried out through a qualitative method using a case study approach. The first semester students, consisting of 13 female and 5 male students, majoring in Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…The ubiquity of digital technology in education had catalyzed related studies on how to facilitate EFL reading comprehension. Pitaloka et al (2020) carried out a case study regarding the impact of blended learning on reading course for EFL undergraduates in South Sumatera, and found that blended learning benefited undergraduates in EFL reading class with flexible learning, understandable materials, and variations in learning approaches. It provided some advice for designing blended reading course such as time management for reading exercises, and convenient accessible platform.…”
Section: Review Of the Related Studies On Efl Reading Achievementmentioning
confidence: 99%
“…The ubiquity of digital technology in education had catalyzed related studies on how to facilitate EFL reading comprehension. Pitaloka et al (2020) carried out a case study regarding the impact of blended learning on reading course for EFL undergraduates in South Sumatera, and found that blended learning benefited undergraduates in EFL reading class with flexible learning, understandable materials, and variations in learning approaches. It provided some advice for designing blended reading course such as time management for reading exercises, and convenient accessible platform.…”
Section: Review Of the Related Studies On Efl Reading Achievementmentioning
confidence: 99%
“…To keep up with the current dynamic world, the educational field is continually changing (Pitaloka et al, 2020), and one recent trend is blended learning. Blended learning is a logical and natural evolution of the learning environment (Ghazizadeh & Fatemipour, 2017;Thorne, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Blended learning combines both in-class and online instruction to attain the strengths of both instruction modes (Albiladi & Alshareef, 2019;Bataineh & Mayyas, 2017;Pitaloka et al, 2020). In blended learning, online instruction does not displace traditional classroom teaching but rather adds a further dimension to the learning experience (Sheerah, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations